Distinct features of hypereosinophilic syndrome with neuropathy from eosinophilic granulomatosis with polyangiitis - Takeuchi, Hiroki; Kawamura, Kazuyuki; Kawasaki, Teruaki; Oka, Nobuyuki (Frontiers in Neurology, 2022)
Background and Objectives: Hypereosinophilic syndrome (HES) and eosinophilic granulomatosis with polyangiitis (EGPA) have overlapping clinical considerations, which frequently involve peripheral neuropathy. The current study aimed to discriminate between the clinicopathological features of HES and EGPA, focusing on the mechanism of peripheral nerve damage. Methods: A total of 53 patients who underwent nerve biopsies at our laboratory were examined: nine patients with idiopathic HES (iHES), three patients with reactive HES, 14 patients with myeloperoxidase-anti-neutrophil cytoplasmic antibody (ANCA)-positive EGPA, and 27 patients with negative EGPA. Nerve biopsies were performed using light and electron microscopy. Results: Polyneuropathy was more common than mononeuritis multiplex in iHES, which differed from that in ANCA-negative EGPA groups (p = 0.012). Nerve biopsies showed that iHES was associated with neuropathy features such as rare vasculitis and non-vasculitic eosinophilic infiltrates, which differed from those of ANCA-negative EGPA. Fibrinoid necrosis was found only in the reactive HES and ANCA-positive groups. The percentage of endoneurial vessels occluded with eosinophils tended to be higher in iHES (1.8%) than in ANCA-positive EGPA (0%) and negative EGPA (0.7%). In a patient with ANCA-negative EGPA, the endoneurial vessels were occluded with platelets, fibrinoid materials, and eosinophils, demonstrating the morphology of eosinophil extracellular traps. Conclusion: iHES with neuropathy showed a pattern more similar to polyneuropathy than mononeuritis multiplex, which is dominant in ANCA-negative EGPA, and tended to show vasculitis in the peripheral nerves less frequently compared with EGPA. Eosinophilic infiltration and endoneurial vascular occlusion by eosinophils may cause nerve damage.